Variants in CPT1A, FADS1, and FADS2 are Associated with Higher Levels of Estimated Plasma and Erythrocyte Delta-5 Desaturases in Alaskan Eskimos - Voruganti, V. Saroja; Higgins, Paul B.; Ebbesson, Sven O.; kennish, John; Goring, Harald H.; Haack, Karin; Laston, Sandra; Drigalenko, Eugene; Wenger, Charlotte R.; Harris, William; Fabsitz, Richard R.; Devereux, Richard B.; et al. (Frontiers in Genetics, 2012)
The delta-5 and delta-6 desaturases (D5D and D6D), encoded by fatty acid desaturase 1 (FADS1) and 2 (FADS2) genes, respectively, are rate-limiting enzymes in the metabolism of ω-3 and ω-6 fatty acids. The objective of this study was to identify genes influencing variation in estimated D5D and D6D activities in plasma and erythrocytes in participants of the GOCADAN (Genetics of Coronary Artery Disease in Alaska Natives) study. Desaturase activity was estimated by product: precursor ratio. We found evidence of linkage for estimated erythrocyte D5D (eD5D) on chromosome 11q12-q13 (LOD=3.5). The confidence interval contains candidate genes FADS1, FADS2, 7-dehydrocholesterol reductase (DHCR7), and carnitine palmitoyl transferase 1A, liver (CPT1A). Measured genotype analysis found association between CPT1A, FADS1, and FADS2 single-nucleotide polymorphisms (SNPs) and estimated eD5D activity (p-values between 10-28 and 10-5). A Bayesian quantitative trait nucleotide analysis showed that rs3019594 in CPT1A, rs174541 in FADS1, and rs174568 in FADS2 had posterior probabilities >0.8, thereby demonstrating significant statistical support for a functional effect on eD5D activity. Highly significant associations of FADS1, FADS2, and CPT1A transcripts with their respective SNPs (p-values between 10-75 and 10-7) in Mexican Americans of the San Antonio Family Heart Study corroborated our results. These findings strongly suggest a functional role for FADS1, FADS2, and CPT1A SNPs in the variation in eD5D activity.